PENGARUH IMPOR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Muhamad Subhan; M. Yunus; Robi Agustin (Al-Iqtishad: Jurnal Ekonomi Syariah, 2021)
Economic growth is a measure of the progress of an economic movement. Islamic economic growth has existed during the dialogue of classical Muslim thought, namely the so-called "prosperity of the earth". The term prosperity of the earth contains knowledge related to economic growth, according to what Ali bin Abi Talib Radhiyallahu Anhu conveyed to the governor in Egypt: ???You should pay attention to land prosperity with a higher concern than tax collection, because the tax can be increased by making land prosperous. Whoever collects taxes without considering the welfare of the land, the nation is headed for destruction???. Some of the basic knowledge related to economic growth is viewed from the perspective of sharia, namely a description of economic problems. Islam explains that the case is in line with the role prepared by Allah Subhanahu Wa Ta'ala for human needs in order to solve the problems of human life. Export and import activities generate many benefits for the participating countries. This study looked at the effect of the import variable on the economic growth variable in Jambi province. The method used is simple correlation and regression analysis. The result of using correlation analysis shows that there is a very strong positive relationship between the import variable and the economic growth variable. Based on the results of simple regression analysis, there is an influence between the import variables on the economic growth variable. Every increase in imports of 1 billion rupiah so that it will increase economic growth, namely 1.433 billion rupiah. The coefficient of determination (R2) is 77.39%, meaning that the diversity of economic growth can be explained by imports. Furthermore, 22.61% is explained by other variables that are not included in the regression model.